2014
DOI: 10.1093/aob/mcu246
|View full text |Cite
|
Sign up to set email alerts
|

Zinc induces distinct changes in the metabolism of reactive oxygen and nitrogen species (ROS and RNS) in the roots of twoBrassicaspecies with different sensitivity to zinc stress

Abstract: The results indicate a clear relationship between ROS and RNS metabolism as a mechanism of response against stress caused by an excess of Zn. The oxidative stress components seem to be more dominant than the elements of the nitrosative stress in the root system of these two Brassica species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 69 publications
12
60
0
Order By: Relevance
“…Plants undergoing metal stress result in series of signaling events that largely includes reprogramming of transcripts that could help them to overcome the toxicity. In plants, excess of Zn also results in the generation of reactive oxygen and nitrogen species (Feigl et al, 2015). The abundance of multiple membrane proteins is increased by the presence of either excess Zn or Fe deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Plants undergoing metal stress result in series of signaling events that largely includes reprogramming of transcripts that could help them to overcome the toxicity. In plants, excess of Zn also results in the generation of reactive oxygen and nitrogen species (Feigl et al, 2015). The abundance of multiple membrane proteins is increased by the presence of either excess Zn or Fe deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, lipid oxidation is not a phenomenon restricted to seed aging; instead, it plays a role in many processes, like photooxidative stress (Broin and Rey, 2003), drought-induced leaf damage (Avramova et al, 2017), and metal-induced root damage (Feigl et al, 2015). Also, numerous studies in the fields of microbiology (Imlay, 2013) and medicine (Ames et al, 1993) link lipid oxidation to biological questions of great relevance, like pathogen defense, aging, and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…for photosynthesis. Feigl et al (2015) reported that a Zn treatment significantly increased the Cu and Fe contents but decreased the Mn content in the roots of Brassica, compared with the control. Zn and Cu use the same transporters, which can be upregulated by excess Zn, although Cu is preferred (Fraústo da Silva & Williams, 2001).…”
Section: Effects Of Zn Treatments On Volume and Zn Content Of Guttatimentioning
confidence: 98%